Selective MMP-inhibition with Ro 28-2653 in acute experimental stroke: a magnetic resonance imaging efficacy study - Nagel, Simon; Heinemann, Philipp von; Heiland, Sabine; Koziol, J.; Gardner, H.; Wagner, Simone (Brain research, 2011)
Blood-brain-barrier (BBB) breakdown due to matrix metalloproteinase (MMP) activity following stroke is often associated with cerebral edema, larger infarct volumes and bad outcome. In the present study we examined a novel MMP-inhibitor (Ro 28-2653) with high selectivity for MMP2, MMP9 and membrane type 1-MMP in an acute stroke model comparing two different treatment regimens. We subjected rats to 90min of focal cerebral ischemia followed by 3days or 7days of reperfusion, respectively, using the middle cerebral artery (MCA) filament occlusion technique. Ro 28-2653 was administered daily in a vehicle solution for 2days or 6days after ischemia, respectively. We assessed the behavior with a functional neuroscore and infarct volumes as well as blood-brain-barrier (BBB) breakdown with magnetic resonance imaging (MRI) after 3 and 7days. Infarct edema volumes, BBB breakdown and behavior at 3days were significantly attenuated in rats treated for 2days with Ro 28-2653 as compared to vehicle and untreated controls. After 6days of treatment however, infarct and BBB breakdown volumes as well as behavior did not differ significantly between the groups at 7days. The new high selective MMP-inhibitor Ro 28-2653 significantly reduced brain injury only when administered in the first 2days after focal cerebral ischemia. Prolonged treatment for 6days did not show any beneficial effects possibly due to interference with protective restorative processes.
First published online: 21 October 2010
Gesehen am 15.09.2022